Manajemen Praktik Kerja Lapangan (PKL) Berbasis Kemitraan Industri pada Sekolah Menengah Kejuruan (SMK) di Provinsi Kalimantan Tengah - Aprianto (FKIP Universitas Palangka Raya, 2026)
The implementation of Field Work Practice (Internship/On-the-Job Training) is a vital element in vocational education as it bridges the gap between school-based theory and the needs of the industrial world. This study aims to analyze the management of Field Work Practice (FWP/PKL) in Vocational High Schools (SMKs) in Central Kalimantan Province, covering the aspects of planning, implementation, and evaluation. The research employed a qualitative descriptive method, with data collected through interviews, observations, and documentation studies conducted at three selected SMKs in Palangka Raya and its surrounding areas. The results show that: (1) PKL planning has been implemented well; however, the mapping of local industry competencies (plantation and mining sectors) needs to be further strengthened; (2) the implementation of PKL is constrained by less intensive monitoring due to geographical distance; and (3) evaluation is still dominated by technical aspects and places insufficient emphasis on soft skills. The study concludes that it is necessary to optimize the role of the PKL Working Group (Pokja PKL) and to digitalize the monitoring system in order to improve the effectiveness of the program in Central Kalimantan.